0787 Descriptive Epidemiology of Obstructive Sleep Apnea in Children with Autism Spectrum Disorder. (27th April 2018) - Harris, J; Malow, B; Werkhaven, J
Abstract: Introduction: Sleep disturbances in pediatric patients have been discussed heavily in published literature, but limited attention has been given specifically to obstructive sleep apnea (OSA) in those with autism spectrum disorder (ASD). Our objective is to investigate the association between OSA and ASD in this patient population. Methods: Children with ASD evaluated for OSA from January 2006 through December 2016 at our institution were identified using the Synthetic Derivative, a multi-source database of de-identified clinical and demographic data. Descriptive statistics and analyses were performed. Results: In the study population of 6794 children with ASD ages 2 to 18 years, 543 children were identified with a diagnosis of OSA representing a point-prevalence of approximately 8% in the population. The age distribution was unimodal, with patients between the ages of 6–12 years making up the largest percentage (11.2 ± 3.7). The percentage of white (65.9%) patients outnumbered African American (17.1%), Hispanic (11.7%) and Asian (3.2%) patients combined. Of the patients treated for OSA, the majority (69.6%) underwent surgical therapy - adenotonsillectomy (43.8%), adenoidectomy (19.9%), or tonsillectomy (5.9%). A smaller proportion received medical therapy (32%), either in addition to or in lieu of surgery - intranasal corticosteroids (fluticasone), anti-inflammatory modulators (montelukast), continuous positive airway pressure (CPAP), and/or supplemental oxygen. Conclusion: Our findings suggest that OSA is much more prevalent in children with ASD than those who are typically developing (literature prevalence of 1–4%). In children with ASD, OSA tends to be treated surgically more often than medically. Given that challenging behaviors are common in children with ASD, and are often exacerbated by sleep disturbance, treatment of OSA in ASD may be an important avenue for improving daytime functioning as well as overall health in this population. If confirmed in independent datasets, our findings suggest that patients with ASD be screened routinely for symptoms of OSA. Support (If Any):